One Health for Food Safety, Food Security, and Sustainable Food Production - Garcia, Sara N.; Osburn, Bennie I.; Jay-Russell, Michele T. (Frontiers in Sustainable Food Systems, 2020)
Globally, our society faces an enormous challenge to feed, house and provide a healthy life for the growing human population while preserving the environment and natural resources for the benefit of future generations. In order to meet these challenges, sustainable food production and environmental stewardship is paramount and will require a One Health approach. One Health is the concept that the health of humans, animals, and the environment are inextricably linked. This approach can be applied to food safety, sustainable food production and environmental stewardship by bringing together interdisciplinary teams to create a One Health network to address these challenges. Farmers, consumers, researchers, government agencies, and consumer advocacy groups play an important role in influencing food safety policies and sustainable food production practices. To make progress towards improving food safety and best practices for sustainable food production, scientific research is vital to shape and inform policies, practices and advance technological applications to increase food production, improve sustainable practices, and assess environmental impact in order to meet global health challenges, safeguard the environment, and provide an economic benefit to agriculture producers. Incorporating One Health education into curriculum for medical, veterinary, and scientific programs to develop one health competencies and networks is needed for improving public health, food safety and sustainable agriculture.